2017
DOI: 10.3390/ijerph14040429
|View full text |Cite
|
Sign up to set email alerts
|

Health Risk Assessment of Indoor Air Quality, Socioeconomic and House Characteristics on Respiratory Health among Women and Children of Tirupur, South India

Abstract: Background: Indoor air pollution is still considered as one of the leading causes of morbidity and mortality worldwide and especially in developing countries, including India. This study aims to assess social, housing, and indoor environmental factors associated with respiratory health among mothers and children. Methods: The study was conducted in the city of Tirupur, South India. We quantitatively assessed the indoor exposure to fine particulate matter (PM2.5) and carbon monoxide in relation to respiratory h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 19 publications
4
30
2
4
Order By: Relevance
“…In Tirupur, South India, researchers found that in addition to homes with closed windows while cooking, and homes that allowed for smoking indoors, the highest biomass burning exposures were present in households with low socio economic status. Specifically, households with income less than 1,000 Indian Rupees (21 US Dollars) had residents who reported higher frequency of respiratory health systems [14]. Similar observations were also found in all other studies included in this review.…”
Section: Socio-economic Statussupporting
confidence: 84%
See 2 more Smart Citations
“…In Tirupur, South India, researchers found that in addition to homes with closed windows while cooking, and homes that allowed for smoking indoors, the highest biomass burning exposures were present in households with low socio economic status. Specifically, households with income less than 1,000 Indian Rupees (21 US Dollars) had residents who reported higher frequency of respiratory health systems [14]. Similar observations were also found in all other studies included in this review.…”
Section: Socio-economic Statussupporting
confidence: 84%
“…Mud house built in study area in Nepal [6] In Tirupur, South India, real time monitoring in 80 households was conducted with DustTrack Aerosol Monitor Model 8520 (TSI Inc, Shoreview, MN, USA) for PM2.5 particles at flow rate of 1.7 L/min. The CO levels were measured using Draeger pump (Model 21/31) which measured CO from lower limit of detection of 2.47 mg/m 3 up to 74 mg/m 3 [14].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paparan dalam ruangan terhadap partikulat halus (PM 2,5 ) meningkatkan gejala pernafasan pada wanita dan anak-anak pada rumah tangga berpenghasilan rendah, dan mereka yang memiliki kebiasaan merokok di dalam rumah. 26 Karakteristik risiko pada siswa ditentukan dari hasil perbandingan antara nilai intake dengan nilai dosis referensi (RfC), maka semakin besar intake maka akan semakin besar risikonya. Berdasarkan perhitungan risiko realtime, 3 tahun dan 12 tahun pada siswa didapatkan bahwa RQ<1 artinya siswa kelas VIII yang menjadi sampel penelitian belum memiliki risiko kesehatan akibat dari pajanan PM 2,5 di lingkungan sekolah, karena intake yang masuk ke dalam tubuh masih pada batas aman.…”
Section: Pendahuluanunclassified
“…Emissions from industrial or traffic related sources are essentially under legislation, but residential combustion of biomass fuels, agricultural burning, and forest fires are largely uncontrolled and may result in particle concentration up to 3 mg/m 3 or even higher. 3 , 8 Particles less than 2.5 μm (fine particles; PM 2.5 ), are considered to be particularly harmful, as they efficiently evade the mucociliary defense system and are deposited in the peripheral airways, where they can exert their pathophysiological mechanisms, linking exposure to ambient fine particles to diseases. 9 …”
Section: Introductionmentioning
confidence: 99%